Analysis of Verbal Fluency in Slovenian Language in Patients With Schizophrenia - Žabkar, Jure; Marinković, Mila; Rus Prelog, Polona; Zakšek, Martina (Proceedings of the10th Student Computing Research Symposium (SCORES’24), 2024)
This study investigates verbal fluency in the Slovenian language among individuals diagnosed with schizophrenia compared to healthy controls. Participants completed a verbal fluency task, which involved producing as many words as possible starting with a specific letter in Slovenian within a set time limit. The analy-sis included statistical testing and semantic similarity measures using FastText embeddings. Significant differences were found between the groups in terms of the number of correct and total words produced. While semantic similarity showed minimal dif-ferences, global optimality divergence revealed notable disparities. These findings highlight the utility of comprehensive analytical approaches in understanding verbal fluency deficits in schizophre-nia, emphasizing the need for nuanced methods to capture the complexity of cognitive impairments in this population.